Analisis Pengaruh Bauran Pemasaran Terhadap Keputusan Konsumen Memilih Beras Kepala Merek Buah Pinang Di Kabupaten Pinrang - Deri Alikram Nurdin; Milka Pasulu; hafipah hafipah (Jurnal Online Manajemen ELPEI, 2022)
This research is a type of correlational quantitative research. measurement using multiple linear regression test. 120 samples were taken from 350 populations using data collection techniques through questionnaires and documentation. The data obtained was processed using statistical methods, namely through descriptive analysis and quantitative analysis. Based on the research results, it was found that the results of the regression calculations in this table show that the coefficient of determination (adjusted R square) obtained is 0.912. this means that 91.2% of consumers' purchasing decisions for betel nut brand rice are influenced by product variables (X1), price (X2), location (X3) and promotion (X4) while the remaining 8.8% are influenced by other variables not examined in this study . Simultaneously there is an influence between product, price, distribution, and promotion on consumer decisions to choose betel nut brand rice in Pinrang Regency. It is expected that the price of Kepala Nasi in the market does not differ much from one brand to another, so that it will have a significant influence on the purchasing decision of the Areca Kelapa brand in Pinrang Regency. For researchers it is hoped that in the research that will be carried out it will expand the range of samples and increase research tests so that the results are more accurate in measuring the influence of the market mix on consumer decisions